Automatic Diachronic Normalization of Polish Texts - Jassem, Krzysztof; Graliński, Filip; Obrębski, Tomasz; Wierzchoń, Piotr (Investigationes Linguisticae, 2018)
The paper presents a method for the automatic diachronic normalization of Polish texts – the procedure, which, for a given historical text, returns its contemporary spelling. The method applies finite-state transducers, defined in a sublanguage of the Thrax formalism. The paper discusses linguistic issues, such as evolution in spelling of the Polish language, as well as implementation aspects, such as efficiency or testing the proposed method.